2002
DOI: 10.1016/s0966-9795(01)00078-4
|View full text |Cite
|
Sign up to set email alerts
|

Formation, modulation and adaptive twinning of martensite in the Au7Cu5Al4 shape memory system

Abstract: The Au 7 Cu 5 Al 4  electron phase transforms displacively from an L2 1 parent to a nominally bodycentred tetragonal martensite with c/a<1. The compound is of interest because it has the potential to serve as an 18 carat shape memory alloy in jewellery. Analysis of its X-ray diffraction spectra indicates that the martensite is modulated by a [110]/[ 10 1 ] transverse shear wave, showing that it belongs, strictly speaking, to the generic B19 structure type. The martensite is also twinned, and the probable twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…At higher magnification, fringes spaced at about 1.54 nm become visible in this film. If a nominal spacing of the close-packed planes of 0.222 nm is accepted [10,18], then a martensite phase of the 7R type is indicated by the presence of these fringes [10]. The lack of crystallinity when the (Au 0.58 Cu 0.42 ) 1-x Al x films were deposited at room temperature is similar to the situation found for very thin, nanoscale films of TiN [14].…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…At higher magnification, fringes spaced at about 1.54 nm become visible in this film. If a nominal spacing of the close-packed planes of 0.222 nm is accepted [10,18], then a martensite phase of the 7R type is indicated by the presence of these fringes [10]. The lack of crystallinity when the (Au 0.58 Cu 0.42 ) 1-x Al x films were deposited at room temperature is similar to the situation found for very thin, nanoscale films of TiN [14].…”
Section: Resultssupporting
confidence: 52%
“…It has been shown to be relatively resistant to aging compared to its copper-based counterparts and has been previously studied in its bulk form [2][3][4][5][6][7][8][9][10][11][12]. However no work has been done on any thin film or nanostructured properties.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of some of the less familiar phases were subsequently determined, and are reported elsewhere [9][10][11]. The degree of ordering of the AuCu-I phase was primarily determined by computation of the ratio a/c, determined for a four-atom fct (a/c>1) or bct unit cell (a/c<1).…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…In contrast, laths were barely evident or absent in the as-cast, arc-melted and unmounted state. X-ray diffraction studies conducted at ambient and elevated temperatures revealed that the lathy phase at room temperature has the structure of a nominally tetragonal martensite [10], the atomic positions of which are further modulated [11]. The parent phase for this martensite is a little-known ternary β electron phase, with the nominal composition Au 7 Cu 5 Al 4 and an e/a ratio of 1.48 [9].…”
Section: The β Phase Fieldmentioning
confidence: 99%
“…The martensite phase transformed from the ordered L2 1 phase has a modulated body-centered tetragonal structure with the martensitic transformation starting temperature (Ms) of about 296 K [3,4]. The disordered A2 phase quenched into liquid nitrogen can also transform to martensite with the Ms below 273 K. However, the ordered B2 phase cannot transform to martensite even quenched into liquid nitrogen [5].…”
Section: Introductionmentioning
confidence: 99%